Fluctuations of serum and bile lipid concentrations during the menstrual cycle. Issue 6076 (18th June 1977) - Low-Beer, T S; Wicks, A C; Heaton, K W; Durrington, P; Yeates, J
Abstract : We measured fasting serum and bile lipid concentrations at three intervals during the normal menstrual cycles of 11 healthy women not taking oral contraceptives. In nine of them cholesterol saturation of bile, and therefore presumably the risk of developing gall stones, was higher nine days after midcycle than at the end of menstruation. This change in bile cholesterol saturation was preceded by a significant fall in serum lipid concentrations: during the nine days after mid-cycle serum triglyceride and cholesterol concentrations fell in nine and eight of the 11 women respectively. Changes in the composition of serum and biliary lipids during the menstrual cycle are presumably due to a direct effect of sex hormones on the liver.